A Long and Fruitful Cooperation in Atmospheric Aerosol Research between Cuba and Spain - Antuna-Marrero, Juan Carlos; de Frutos, Angel; Estevan, Rene; Cachorro, Victoria; Barja Gonzalez, Boris; Mogo, Sandra; Rodriguez-Vega, Albeht; Toledano, Carlos; Garcia, Frank; Mateos, David; Antuna-Sanchez, Juan Carlos; Gonzalez, Ramiro; et al. (My University, 2025)
Cuban and Spanish scientists have been studying the properties of atmospheric aerosols in Camagüey, Cuba, for more than 15 years, achieving notable scientific results at the local, regional, and global levels. Using instruments and expertise supplied by Spain, Cuban scientists have characterized local aerosol optical and microphysical properties and their chemical composition and optical absorbing properties. Aerosol optical depth (AOD) and Ångström exponent observations were used to validate MODIS satellite observations and broadband AOD from local pyrheliometers. Sun photometer cloud optical depth allowed us to characterize local cloudiness and its radiative forcing. Scientific work included climatologies of the solar radiation for the last four decades at Camagüey and of aerosols in the Caribbean basin in the last two decades. Another result was designing, building, and processing of a low-cost all-sky camera. Besides scientific results, the cooperation allowed the Cuban sun photometer observations to contribute to the Red Ibérica de Medida Fotométrica de Aerosoles and AERONET. A workshop celebrating 10 years of cooperation was held at Camagüey in 2016. The workshop participants evaluated the progress, difficulties, and challenges and inaugurated a Spanish angular calibration bench for solar radiation sensors at Camagüey. The workshop also included the first visit of a NASA scientist to Cuba, the only one visit. Cuban scientists became members of the International Science Team of the NASA Tropospheric Emissions: Monitoring of Pollution (TEMPO) satellite mission, just launched, participating in its prelaunch activities. Considering the joint capabilities we developed, Cuban-Spanish contribution is expected for the TEMPO postlaunch validation campaign.
Keywords: atmosphere; central america; aerosols; radiation; in situ atmospheric observations; aerosol optical properties